Oesophagus / Esofago (C15.9) - Prognostic significance of preoperative serum CA 72-4 and CA 242 in patients with esophageal squamous cell carcinoma - Feng, Ji-Feng; Huang, Ying; Chen, Qi-Xun (European Journal of Oncology and Environmental Health, 2014)
Aims: The aim of this study was to determine the prognostic value of CA 72-4 and CA 242 in esophageal squamous cell carcinoma (ESCC). Materials and Methods: From January 2006 to December 2007, a retrospective analysis of 192 consecutive patients with ESCC was carried out. Univariate and multivariate analyses were performed to evaluate the prognostic parameters. Results: The positive rates for CA 72-4 and CA 242 were 18.8% (36/192) and 7.3% (14/192), respectively. Patients with CA 72-4 ≤6 U/ml showed a significantly better 5-year overall survival than patients with CA 72-4 >6 U/ml (42.3% vs. 5.6%; p10 U/ml (37.6% vs. 7.1%; p=0.011). Multivariate analyses demonstrated that differantiation (p=0.021), CA 72-4 (p=0.037), T grade (p=0.012) and N staging (p